Listener Loyalty to B'due Radio: Impact of Broadcast Quality and Brand Image - Juhari, Juhari; Masri, Desi; Zufriady, Zufriady; Zakaria, Nor Balkish (Integrated Journal of Business and Economics (IJBE), 2025)
Radio as an important medium for delivering information and entertainment is facing increasingly intense competition in the media industry. This study aims to examine the direct influence of broadcast quality and brand image on listener loyalty to B'Due Radio, with listener satisfaction acting as a mediating variable. This study uses a quantitative approach with a survey method, distributing questionnaires to 90 B'Due Radio listeners, including teenagers, BKKBN activity group members, FP cadres, field officers, and employees. The data were analyzed through Structural Equation Modelling (SEM) using the Smart PLS-3 software. The results indicate that both broadcast quality and brand image directly affect listener satisfaction, which in turn is associated with greater listener loyalty. Additionally, listener satisfaction mediates the relationship between broadcast quality, brand image, and listener loyalty. The study faces several limitations, such as a small sample size and difficulties in generalizing the results to a wider population. Nonetheless, these findings offer valuable insights into the factors that drive listener loyalty in radio. The results of this study can serve as recommendations for B'Due Radio to enhance broadcast quality, strengthen brand image, and improve listener satisfaction to bolster listener loyalty.